Radion Production in yu - Collisions - Thuy, Dao Thi Le; Giang, Bui Thi Ha (VNU Journal of Science: Mathematics - Physics; Vol 31 No 3, 2015)
We have calculated the cross – section of the  yu-pu   process in the Randall – Sundrum  model, which address the Higgs hierarchy problem in particle physics. Based on the results we have showed that the radion can give observable values at the high energy if the radion mass is in order of GeV. Keywords: Radion, electron, cross – section.